2018
DOI: 10.1002/ajoc.201800340
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Three‐Component Assembly of Fully Substituted 1,2,3‐Triazoles

Abstract: A practical domino three‐component protocol involving aldehydes, amines, and α‐diazo‐β‐ketosulfones provides efficient access to fully substituted 1,2,3‐triazoles. The process proceeds through a tandem Schiff‐base formation and 1,3‐dipolar cycloaddition to generate a key sulfonyltriazoline intermediate, which subsequently undergoes an oxidative aromatization with the aid of air or iodine. The three‐component protocol obviates the need of expensive metal catalysts, proceeds under mildly basic conditions, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 99 publications
0
20
0
Order By: Relevance
“…However, the reaction did not afford the expected triazole; instead, sulfonyltriazole 32 was obtained as the major product in moderate yield. [32] The subsequent screening revealed that K 2 CO 3 /EtOH is the optimal combination to furnish the sulfonyltriazoles in 75 % yield after 72 h. However, the oxidative conversion of the initially generated triazoline to triazole was sluggish and appeared to be the primary reason for the low yield of the product. Thus, the use of I 2 as an external oxidant was crucial for the reaction.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…However, the reaction did not afford the expected triazole; instead, sulfonyltriazole 32 was obtained as the major product in moderate yield. [32] The subsequent screening revealed that K 2 CO 3 /EtOH is the optimal combination to furnish the sulfonyltriazoles in 75 % yield after 72 h. However, the oxidative conversion of the initially generated triazoline to triazole was sluggish and appeared to be the primary reason for the low yield of the product. Thus, the use of I 2 as an external oxidant was crucial for the reaction.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…No final product was observed, and only 42 was achieved in good yield. However, 42 was effectively transformed into the corresponding product with excellent yield in the presence of molecular iodine (Scheme 15) [45]. protocol provides diverse double C-and N-vinylated 1,2,3-triazole derivatives and C-vinylated 1,2,3-triazole derivatives from azidophilic substrates and different azide derivatives.…”
Section: Review Metal-free Synthesis Of Fully Decorated Triazolesmentioning
confidence: 99%
“…Because of the faster hydrolysis of the in situ generated imine intermediates, aromatic aldehydes containing electron-withdrawing substituents afforded no product in the reaction. It was proved that a variety of aliphatic primary amines can efficiently produce the triazole products ( Scheme 14 ) [ 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, in contrast with the previous example, aldehydes bearing EWG-substituents in the aryl moiety failed to deliver the product. An analogous protocol for the preparation of triazole-4-sulfones have been reported by this group [ 195 ].…”
Section: Azoles With Three Heteroatomsmentioning
confidence: 99%